2022
DOI: 10.5946/ce.2021.115
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification in Cancer Patients with Acute Upper Gastrointestinal Bleeding: Comparison of Glasgow-Blatchford, Rockall and AIMS65, and Development of a New Scoring System

Abstract: In a recent series of patients with cancer at the Cancer Institute of Sao Paulo, we found that tumor bleeding was the main cause of upper gastrointestinal bleeding (UGIB; 23.8%), followed by varices (19.7%) and ulcers (16.3%). 1 The rates of mortality from UGIB in the general population ranges from 3.5% to 20%, 2,3 and it is even higher in cancer patients presenting with overt UGIB, approaching 45%. 1 It is recommended that patients with UGIB should be stratified into low or high risk of needing early hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A retrospective study of six scoring systems (AIM65, GBS, MAP, T-score, ABC and pre-endoscopic Rockall score) found that the accuracy for mortality was highest for ABC score followed by MAP (similar to our study), while for predicting intervention, pre-endoscopic Rockall score was the only useful score. In cancer patients with acute UGIB, AIM65 was better than GBS or Rockall score in predicting mortality (AUC 0.84) [ 33 ]. Another study of 5 scores (pre-RS, full-RS, GBS, modified GBS and AIM65) and 7 outcomes found that the need for transfusion and for surgery was predicted by GBS and modified GBS, 30-day mortality by both pre-endoscopic and full Rockall score but also by AIM65, and the need for endoscopic therapy and admission in ICU was predicted by all 5 scores; none of the scores predicted rebleeding risk [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of six scoring systems (AIM65, GBS, MAP, T-score, ABC and pre-endoscopic Rockall score) found that the accuracy for mortality was highest for ABC score followed by MAP (similar to our study), while for predicting intervention, pre-endoscopic Rockall score was the only useful score. In cancer patients with acute UGIB, AIM65 was better than GBS or Rockall score in predicting mortality (AUC 0.84) [ 33 ]. Another study of 5 scores (pre-RS, full-RS, GBS, modified GBS and AIM65) and 7 outcomes found that the need for transfusion and for surgery was predicted by GBS and modified GBS, 30-day mortality by both pre-endoscopic and full Rockall score but also by AIM65, and the need for endoscopic therapy and admission in ICU was predicted by all 5 scores; none of the scores predicted rebleeding risk [ 3 ].…”
Section: Discussionmentioning
confidence: 99%